Urban planning, Covid-19 and sex-gender diversities in Pereira, Colombia - Miguel Peraza (Íconos)
The incorporation of a sex-gender diversity approach in the Plan of Territorial Organization of the city of Pereira, Colombia, constitutes a historical achievement in the current scenario of institutional resistance to public policies that contemplate sexual differences. This article analyzes this achievement of the LGBTI population – specifically trans, within the power structure of a masculinized nation state, whose agents are in charge of territorial planning. Feminist theories, geographies of sexuality, and queer theories merged, with the aim of explaining the connection between these policies, the subjects involved, and the occupation of territory for sex work. The methodology used is qualitative, as an in-depth interview was applied and the criteria of an urban design manual were reviewed, in order to describe the relationship between the actors during the inclusion of the trans population and sex trade zones in the ordinance plan (2015) and its reform project (2017). The analysis was extended to the Covid-19 pandemic scenario to identify how, despite this achievement, trans subjects were again excluded from the statistics and policies applied following confinement. It is concluded that the Pereira experience reveals the importance of including sex-gender diversity in territorial design and planning processes.